Isotopic niches of sympatric native and exotic fish species in a Neotropical floodplain - Philippsen,Juliana S. (2015)
This study investigated the isotopic niches of two fish species, one exotic and one native. It was hypothesized that these species would show little or no isotopic niche overlap. This hypothesis was tested with the isotopic niche concept and the trophic Layman's metrics. A considerable isotopic niche overlap was observed between the species, mainly for the exotic that showed the greater percentage of overlapping, indicating an interspecific competition for food resources. Layman's metrics also showed this species probably exploits a more specific array of food resources when compared with the native species. The native species probably has the ability to exploit a wider array of resources, highlighted by the higher values given for the Layman's metrics. The juveniles and adults of native species showed minor overlapping between the isotopic niches. This indicates that they have probably adopted different foraging strategies, minimizing intraspecific competition. Evidences that the exotic species explores a narrower range of resources and that the native species has a greater isotopic niche and possibly suffer less intraspecific competition, indicates that the native species can tolerate the presence of the exotic species and promote survival and maintenance of its population even under possible competition effects imposed by the exotic species.